The role of Practice in Facilitating Consumer Value Co-Creation in the Higher Education Sector (Revista Lusófona de Economia e Gestão das Organizações, 2016)
Service-Dominant logic provides a framework for refinements in the concepts of valuecreation and co-creation between multiple actors. Moreover, S-D logic provides a shiftfrom outcome to process by arguing that value is not created and delivered in terms ofoutput but rather co-created in a process. Recently, the interest has focused on HigherEducation and how value is co-created between actors in Higher Education. However,it is not yet known, whether the practices within value are co-created in the HigherEducation. Drawing on S-D logic framework and practice theory, the aim of this paperis to develop and understand how practices in Higher Education such as interactingmay offer opportunities to facilitate co-creation and contribute to value in-use in thehigher education sector.